Антропологічний матеріал давньоруського могильника Зеленче - Рудич, Т.О. (Археологія, 2015)
Охарактеризовано антропологічний матеріал з могильника давньоруського часу Зеленче на Тернопільщині та подано результати зіставлення його із синхронними слов’янськими популяціями. Охарактеризован антропологический материал из могильника эпохи киевской руси зеленче Тернопольской обл. Представлен материал из 8 погребений.
Поданы результаты сопоставления его материалов с синхронными популяциями восточных, западных и юж ных славян. Маленькая серия из могильника зеленче и другие группы с територии Галицкой земли отличаются антропологическим своеобразием. Морфологически и статистически они отличаются от долихокранных и ме зокранных масивных популяций волынских, тиверских, древлянских земель. Галицкие серии демонстрируют статистическую близость к ряду териториально отдаленных популяций части западных и южных славян (чехов, лужицких славян, моравцев, хорватов). Это может свидетельстовать в пользу общего происхождения. Described is the anthropological material from the burial ground of kyiv Rus epoch in zelenche of ternopil Oblast. Ana lyzed is the material from 8 graves.
presented are the results of comparison of these materials with synchronous populations of the eastern, Western, and southern slavs. A small series from zelenche burial ground and other groups from halych land territory are distinguished by their anthropological peculiarities. they are morphologically and statistically different from dolichocranic and mesoce phalic massive populations at the lands of the Volynians, the tyvertsi, and the drevlyans. halych series show the statistical closeness to several distant populations of the part of the Western and southern slavs (Czechs, luzhytsia slavs, Moravians, and the Croatians). this fact can testify for their common origin.